Analyzing Regulatory Framework for Carbon Capture and Storage (CCS) Technology Development: A case study approach - Mac Osazuwa-Peters; Margot Hurlbert (The Central European Review of Economics and Management (CEREM), 2020)
Aim: This article provides insight into the portfolio of regulations advancing Carbon Capture and Storage (CCS) deployment. Using a taxonomy of policy portfolio tools adapted for regulations specific to CCS, this research identifies regulatory gaps as well as supports for CCS projects. Design / Research methods: Through a case study approach, this article analyzes the regulatory provisions in six jurisdictions (Texas, North Dakota, the U.S, Saskatchewan, Alberta and Canada) which have a successful CCS facility. Analyzing the provisions and content of regulations in these jurisdictions, this article highlights regulatory supports or areas of gaps for CCS projects in each jurisdiction. Conclusions / findings: There is no uniform definition or categorization of CO2 as a hazard, waste, pollutant or commodity across jurisdictions. This has serious impact on CO2 transport, especially across jurisdictions. It also impacts the administration of storage systems for CCS facilities. Regulations focusing primarily on technical aspects of CCS including capture, transport, and liability predominate while there are less regulatory provisions for the financial aspects of CCS technology as well as public engagement and support. While capital grants and emission and tax credits are the predominant financial issues covered in regulations, contract for differences, streamlining emission trading across borders and enhancing cooperation and multilevel engagement in CCS warrant more attention. Originality / value of the article: Many scenarios to maintain global warming below 2 degrees Celsius require combinations of new technology including CCS. The focus on CCS cost as a barrier to deployment overshadows the needs for regulatory support as a means of reducing uncertainties and de-risking CCS investments.
Keywords: 330